Creativity in problem solving to improve complex health outcomes: Insights from hospitals seeking to improve cardiovascular care - Amanda L. Brewster (Learning Health Systems, 2022)
Abstract Introduction Improving performance often requires health care teams to employ creativity in problem solving, a key attribute of learning health systems. Despite increasing interest in the role of creativity in health care, empirical evidence documenting how this concept manifests in real‐world contexts remains limited. Methods We conducted a qualitative study to understand how creativity was fostered during problem solving in 10 hospitals that took part in a 2‐year collaborative to improve cardiovascular care outcomes. We analyzed interviews with 197 hospital team members involved in the collaborative, focusing on work processes or outcomes that participants self‐identified as creative or promoting creativity. We sought to identify recurrent patterns across instances of creativity in problem solving. Results Participants reported examples of creativity at both stages typically identified in problem solving research and practice: uncovering non‐obvious problems and finding novel solutions. Creativity generally involved the assembly of an “ecological view” of the care process, which reflected a more complete understanding of relationships between individual care providers, organizational sub‐units, and their environment. Teams used three prominent behaviors to construct the ecological view: (a) collecting new and diverse information, (b) accepting (rather than dismissing) disruptive information, and (c) employing empathy to understand and share feelings of others. Conclusions We anticipate that findings will be useful to researchers and practitioners who wish to understand how creativity can be fostered in problem solving to improve clinical outcomes and foster learning health systems.